Harmony Matters: Integrating The Social Communication Models of Leadership As A Key To Building Organizational Harmony - Ulfah, Elok Maria; Muchlis; Bustomi, Abu Amar; Suwadji; Rofik, Abdur (Universitas Islam Raden Rahmat Malang, 2023)
Maintaining harmony among pancak silat organizations is very important. Because lately the potential for conflict between organizations is so strong, which in many cases is driven by hoax information and the issue of inter-group synthesis. In this context, a leadership social communication model is needed to anticipate and reduce the potential for division. The purpose of this research seeks to reveal the integration of the leadership social communication model in an effort to maintain harmony between martial arts college organizations. This research uses a qualitative-explorative approach and is designed in the frame of phenomenological studies. The data collection techniques used were semi-structured interviews, observation and documentation. Then, after the data was collected, the researcher analyzed the data using framework analysis technique. The results of this study indicate that: Leadership social communication models in an effort to maintain harmony between martial arts colleges include: social communication built with youths of youth organizations, social communication built when doing sports with village youths, social communication built in coffee shops, social communication built when there are mutual cooperation activities, social communication built when there are community celebrations, social communication built when religious holidays arrive, and social communication built during the commemoration of independence day. So that based on the integration of the leadership communication model, there is almost no conflict that comes to the surface, both between the administrators and members of the Persaudaraan Setia Hati Terate (PSHT) martial arts college and the Tunas Muda Winongo Madiun martial arts college. This reinforces that the social communication model built by the Village Head as the Village leader gets a positive response from the community. They consider that the leadership social communication model carried out has proven successful in efforts to maintain harmony between existing martial arts organizations.